Authenticity or Image-Making? A Critical Discourse Analysis of KDM’s Political Persona on Social Media - Rossy Halimatun Rosyidah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study investigates how Kang Dedi Mulyadi (KDM) constructs his political identity on social media through emotional storytelling and cultural symbolism. Using a qualitative descriptive method and Fairclough’s three-dimensional Critical Discourse Analysis (CDA), this research analyzes two purposively selected YouTube videos and corresponding public comments. The analysis focuses on textual choices, discursive practices, and socio-cultural contexts to explore how KDM’s identity is performed and received. Findings show that KDM consistently uses Sundanese language, informal speech, and acts of empathy to portray himself as a caring and approachable leader. Public responses reflect trust, emotional engagement, and cultural pride, indicating that his digital persona resonates with grassroots audiences. This study highlights how emotional narratives and local cultural elements can foster political legitimacy and trust in non-Western digital contexts. Limitations include platform bias and limited data scope. Future research should apply cross-platform and mixed-method approaches to examine broader patterns in digital political identity-making.